2018
DOI: 10.1038/s41386-018-0084-y
|View full text |Cite
|
Sign up to set email alerts
|

(2R,6R)-Hydroxynorketamine is not essential for the antidepressant actions of (R)-ketamine in mice

Abstract: (R,S)-Ketamine has rapid and sustained antidepressant effects in depressed patients. Although the metabolism of (R,S)-ketamine to (2 R,6 R)-hydroxynorketamine (HNK), a metabolite of (R)-ketamine, has been reported to be essential for its antidepressant effects, recent evidence suggests otherwise. The present study investigated the role of the metabolism of (R)-ketamine to (2 R,6 R)-HNK in the antidepressant actions of (R)-ketamine. Antidepressant effects were evaluated using the forced swimming test in the lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 28 publications
2
74
1
Order By: Relevance
“…In the presence of CYP inhibitors, ( R )‐ketamine (3 mg/kg) produced antidepressant actions although the dose did not show antidepressant effects in the absence of CYP inhibitors. These results suggest that the production to (2 R ,6 R )‐HNK from ( R )‐ketamine is not necessary for its antidepressant effects . Furthermore, we did not detect any sex difference in the pharmacokinetic profile and the antidepressant actions of ( R )‐ketamine in an LPS‐induced mouse model of depression …”
Section: Enantiomers Of Ketamine and Its Metabolitesmentioning
confidence: 56%
“…In the presence of CYP inhibitors, ( R )‐ketamine (3 mg/kg) produced antidepressant actions although the dose did not show antidepressant effects in the absence of CYP inhibitors. These results suggest that the production to (2 R ,6 R )‐HNK from ( R )‐ketamine is not necessary for its antidepressant effects . Furthermore, we did not detect any sex difference in the pharmacokinetic profile and the antidepressant actions of ( R )‐ketamine in an LPS‐induced mouse model of depression …”
Section: Enantiomers Of Ketamine and Its Metabolitesmentioning
confidence: 56%
“…This is consistent with data showing that (R)-ketamine (parent compound of (2R,6R)-HNK) is a more potent antidepressant than (S)-ketamine (Fukumoto et al, 2017;Yang, Qu, Fujita, et al, 2017;Yang et al, 2018;Yang et al, 2015;Zanos et al, 2016;Zhang et al, 2014). The results of a recent study revealed that preventing metabolism of (R)-ketamine to (2R,6R)-HNK by using cytochrome P450 inhibitors does not prevent the antidepressant-relevant actions of (R)-ketamine, administered at a single dose, in the FST 3 and 24 hr post-treatment in LPS-treated mice (Yamaguchi et al, 2018). In that study, while (2R,6R)-HNK production was reduced, the brain levels of (R)-ketamine were dramatically (g) Following 5 days of training, there were no differences in the latency of the mice to fall from the rotating rod between groups.…”
Section: (A) (B) (D) (C)mentioning
confidence: 99%
“…HNK does not cause dissociation, nor does it increase circulating CORT levels, yet Zanos et al still reported rapid antidepressant effects using this compound. However, as stated previously, this assertion that HNK is necessary and sufficient to generate RAAD effects has come under scrutiny [24]. Future experiments to see if animals treated with subanesthetic doses of ketamine under anesthesia experience a sustained antidepressant effect at 24 hours might help answer the question of whether dissociation is relevant to ketamine's AD effect.…”
Section: Discussionmentioning
confidence: 96%
“…To learn more about the ketamine's initial transient molecular pathways, we utilized a well-established oral CORT stress model to sensitize the system and compare the molecular effects of treatment with ketamine versus its metabolite HNK [22]. Recent work provided evidence that HNK on its own is sufficient for the RAAD effect in rodents, although subsequent work has challenged this assertion [7,23,24]. HNK does not induce psychotropic side effects, making it an attractive RAAD candidate for further investigation [11].…”
Section: Increase In Circulating Cort With Ketamine Treatmentmentioning
confidence: 99%